The complete mitogenome of the endangered white-clawed freshwater crayfish Austropotamobius pallipes (Lereboullet, 1858) (Crustacea: Decapoda: Astacidae). (2nd September 2016) - Grandjean, Frederic; Tan, Mun Hua; Gan, Huan You; Gan, Han Ming; Austin, Christopher M.
Abstract: The Austropotamobius pallipes complete mitogenome has been recovered using Next-Gen sequencing. Our sample of A. pallipes has a mitogenome of 15, 679 base pairs (68.44% A + T content) made up of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a 877 bp non-coding AT-rich region. This is the first mitogenome sequenced for a crayfish from the family Astacidae and the 4 th for northern hemisphere genera.